Exploration of miRNAs in Neolamarckia cadamba and their potential cross-kingdom functions - Jia-Jian He; Rui Ye; Ting Chen; Qian-Yun Xi; Jun-Yi Luo; Hao-Jie Zhang; Jia-Han Wu; Jia-Jie Sun; Yong-Liang Zhang (ExRNA, 2020)
Abstract Neolamarckia cadamba (Roxb.) Bosser (Rubiaceae) is a widespread plant with medicine value and has been used for treating various diseases, such as coughs, fevers, anemia, blood disorders and stomach pains. It had been reported that plant miRNAs might enter mammalian intestines and exert a special ingredient across the different species. However, the knowledge about miRNAs in N.cadamba is scarce. In this study, we first applied high-throughput sequencing to identify miRNAs in N.cadamba. Sequencing revealed a total of 11,285,965 raw reads in the small RNA library of N.cadamba leaves. By bioinformatics analysis, we identified a total of 192 miRNAs, including 167 conserved miRNAs and 25 novel miRNAs, which were distributed among 30 families. Next, we used miRanda to predict the targets of those miRNAs in human, 4030 target genes were predicted. Furthermore, Gene ontology (GO) annotation and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analyses indicated that the identified miRNAs majored in binding, vibrio cholerae infection and insulin signaling, which were likely to provide valuable references for further understanding of medical functions of N. cadamba.